2008
DOI: 10.1086/592836
|View full text |Cite
|
Sign up to set email alerts
|

Size Evolution of the Most Massive Galaxies at 1.7 < z < 3 from GOODS NICMOS Survey Imaging

Abstract: We measure the sizes of 82 massive ( ) galaxies at utilizing deep HST NICMOS datataken in the GOODS North and South fields. Our sample is almost an order of magnitude larger than previous studies at these redshifts, providing the first statistical study of massive galaxy sizes at , confirming the z 1 2 extreme compactness of these systems. We split our sample into disk-like ( ) and spheroid-like ( ) n ≤ 2 n 1 2 galaxies based on their Sérsic indices, and find that at a given stellar mass disk-like galaxies at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
488
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 435 publications
(537 citation statements)
references
References 45 publications
47
488
1
1
Order By: Relevance
“…In addition, they can be very compact but massive. In some cases, at redshift ∼2 they are a factor of up to 6 times smaller in size than galaxies of the same mass today (Daddi et al 2005;Trujillo et al 2007;Buitrago et al 2008;van Dokkum et al 2008;van Dokkum et al 2010;Weinzirl et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they can be very compact but massive. In some cases, at redshift ∼2 they are a factor of up to 6 times smaller in size than galaxies of the same mass today (Daddi et al 2005;Trujillo et al 2007;Buitrago et al 2008;van Dokkum et al 2008;van Dokkum et al 2010;Weinzirl et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Trujillo et al 2006b;Longhetti et al 2007;Cimatti et al 2008;van der Wel et al 2008;Saglia et al 2010;Beifiori et al 2014), and a factor of ∼ 4 since z ∼ 2 (e.g. Trujillo et al 2007;Buitrago et al 2008;van Dokkum et al 2008;Newman et al 2012;Szomoru, Franx & van Dokkum 2012;Barro et al 2013;van der Wel et al 2014). This progressive growth appears to happen mainly at the outer envelopes, as several works have shown that massive (M * 1 × 10 11 M ) passive galaxies at high-redshift have comparable central densities to local ellipticals, suggesting the mass assemble took place mainly at outer radii over cosmic time (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they ruled out any substantial evolution in the stellar mass-size relation for the same early-type galaxies, consistent with the passive evolution scenario. However, the evolution in the stellar mass-size relation has recently been stablished at higher redshifts (Trujillo et al 2007;Buitrago et al 2008) and the combination of Palomar massive galaxies sample and lower stellar masses galaxies from the GEMS survey conducted by Trujillo et al (2007) has shown a perceptible evolution in the stellar mass-size relation of early-type galaxies since z ∼ 0.65.…”
Section: Discussionmentioning
confidence: 99%